2021
DOI: 10.3389/fonc.2021.627947
|View full text |Cite
|
Sign up to set email alerts
|

Potential Value of Radiomics in the Identification of Stage T3 and T4a Esophagogastric Junction Adenocarcinoma Based on Contrast-Enhanced CT Images

Abstract: PurposeThis study was designed to evaluate the predictive performance of contrast-enhanced CT-based radiomic features for the personalized, differential diagnosis of esophagogastric junction (EGJ) adenocarcinoma at stages T3 and T4a.MethodsTwo hundred patients with T3 (n = 44) and T4a (n = 156) EGJ adenocarcinoma lesions were enrolled in this study. Traditional computed tomography (CT) features were obtained from contrast-enhanced CT images, and the traditional model was constructed using a multivariate logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Multivariate logistic regression of the traditional features revealed that increased density of peritumoral adipose tissue was an independent predictor of serosal invasion, which was consistent with the findings of Xu Chang et al. ( 18 ) and Sun et al. ( 35 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Multivariate logistic regression of the traditional features revealed that increased density of peritumoral adipose tissue was an independent predictor of serosal invasion, which was consistent with the findings of Xu Chang et al. ( 18 ) and Sun et al. ( 35 ).…”
Section: Discussionsupporting
confidence: 88%
“…Radiomics is an emerging tool to quantitatively assess lesion characteristics from texture analysis techniques ( 17 ). A recent study showed that a radiomics model had a relatively high diagnostic efficacy for serosal invasion compared with a traditional model based on conventional CT signs ( 18 ). Another radiomics study showed that iodine map (IM) derived from DECT increased the diagnostic value of restaging in advanced gastric cancer patients after NAC ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, neither PET/CT nor MRI is a routine preoperative test for patients with gastric cancer. CT is a common method for preoperative evaluation of patients ( 38 ). Enhanced CT is more commonly used in tumor therapy ( 20 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study explored, for the first time, both. Traditional CT is a commonly used non-invasive examination method for the comprehensive assessment of tumor lesions and adjacent structures (18). Many previous studies have shown that the degree of AEG portal phase enhancement is an important difference between HER2-positive and HER2-negative patients (19,20).…”
Section: Discussionmentioning
confidence: 99%